Agricultural nitrogen and phosphorus balances of Korea and Japan: Highest nutrient surplus among OECD member countries. (1st October 2021) - Lim, Ji Yeon; Islam Bhuiyan, Mohammad Saiful; Lee, Seul Bi; Lee, Jeong Gu; Kim, Pil Joo
Abstract: Excessive nutrient balance is a very crucial issue for environmental hazards. The constant addition of high-amounts of nutrient sources in agricultural production generates negative environmental conditions in Korea and Japan yet to be resolved. Therefore, it is obligatory to comprehend the nutrient (nitrogen (N) and phosphorus (P)) balance that is assessed by the difference between nutrient input and output in the soil surface in Korea and Japan. Among 34 Economic Co-operation and Development (OECD) countries, Korea and Japan had the highest N and P balances and thus both countries are primarily responsible for severe environmental pollution via nutrient release. The cultivable land area in both countries has constantly decreased during 1990–2017 at approximately 20 and 15% in Korea and Japan, respectively. Even N and P use efficiency sharply decreased with increasing N and P balance in both targeted countries. Japanese P balance, Korean N and P balances were decreased after the mid-1990s whereas, Japanese N balance almost unchanged for the last 28 years. Unlike chemical fertilizer input, Korean manure input level significantly increased from 78 kg N ha −1 in 1990 to 157 kg N ha −1 in 2017. Japanese manure input level was higher than that of chemical fertilizer without any big change for the last 28 years. The lion share of high N and P balance in both countries could generate from manure inputs, therefore, the number of livestock and their produced debris need to be used with more cautious for the reduction of national N and P surpluses at a benchmark level. These findings ensure to make a more environment friendly policy that can further reduce nutrient balance as well as improve soil health. Graphical abstract: Image 1 Highlights: Korea and Japan had the highest N and P balances among OECD member countries. Arable land area was rapidly decreased in both countries. Chemical fertilizer input highly decreased in Korea, but not in Japan. High manure input made high nutrient balances in both countries.